Batik MSME Acceptance Model for Technology in Jbatik Application in East Kalimantan, Indonesia - Dita Andansari; Darius Shyafary; Sekta Lonir Oscarini Wati Bhakti; R.A. Kartini Nazam (Journal of Civil Engineering, Planning and Design, 2022)
.  The sub-sector of the creative industry that gives the hugest contribution to the national GDP is the handicraft subsector, followed by the fashion subsector and next is the advertising subsector. Batik handicrafts in East Kalimantan have also been developed into fashion products by starting to hold many fashion events, one of which is made from batik so that batik in East Kalimantan is very potential because, in addition to being included in the handicraft subsector, it is also classified as a fashion subsector where the two subsectors are included in the top three creative industry sub-sectors contributing to national GDP.  Of the several technologies made as a form of process innovation for the batik process, the easiest one to be applied is the use of software to design batik motifs considering that the price is affordable compared to equipment for other stages in the batik process. The development of batik including the use of software technology to make batik motif designs first developed in Java in accordance with the history of batik that batik is indeed a tradition of living on the island of Java. Thus, the development of its innovation outside Java is not as fast as in Java, including in the use of technology as the use of software to design batik motifs. With the background mentioned above, it is necessary to conduct research on the batik MSME acceptance model for technology in the batik application in East Kalimantan, Indonesia.  The methods used were a validity test, reliability test, and Spearman rank correlation test. The result was that the correlation between Perceived Usefulness and the Actual System Use variable had a strong relationship level because the value was 0.859 as well as Perceived Ease of Use with the Actual System Use variable. In addition, both correlation values had a two-asterisk sign so that the value was significant, or in other words, there was a positive and significant relationship between the Perceived Usefulness variable and the Actual System Use variable and also the Perceived Ease of Use with the Actual System Use variable.